MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI SMP NEGERI 7 KOTA TEBING TINGGI - Parulian Sijabat (PGSD Universitas Negeri Medan, 2018)
This study aims to determine student learning activities, and increase student learning outcomes by applying Cooperative Learning Type Make a Match models to integer operating material and class VII fractions as many as 38 students. This research is a classroom action research. In this study 3 cycles were used, consisting of 4 stages, namely planning, implementation, observation, and reflection. Obtained the value of mastery learning the initial test obtained 23.68% (9 students) who completed. After teaching actions with the Cooperative Learning Type Make A match model, the results of observations of students in cycle I were 21% and the student learning outcomes of the first cycle were 42.10% (16 students) were completed. In the second cycle, the results of student observation were 45% and student learning outcomes tests were 55.26% (21 students) were completed. While in the third cycle the results of student observations were 76% and the student learning outcomes test was 86.84,% (33 students) were completed.Keywords: Learning Outcomes, Cooperative Learning, Make a Match.